METAL-ORGANIC FRAMEWORK AND COVALENT ORGANIC FRAMEWORK MEMBRANES FOR MOLECULAR SEPARATIONS - (:unkn) unknown (My University, 2024)
Olefin/paraffin separation as a typical example of gas separation has attracted a lot of research interest because of the high demand for high-purity olefins in the petrochemical industry. However, the physical and chemical similarities of olefins and paraffins make them difficult to separate. It is also critical to separate organic liquid mixtures in the petroleum industry since the consumption of organic solvents is increasing as industries develop, and the problem of recovering and reusing organic solvents is becoming more prevalent. Distillation is the most commonly used separation technology in the industry, but it is an energy-intensive process. As an alternative separation process, membrane technology has become a reliable, energy-efficient, and techno-economically attractive option for separation and purification, especially in chemical and petrochemical industries. Over the past decade, metal-organic frameworks (MOFs) and covalent organic frameworks (COFs) have emerged as appealing materials for molecular separation due to their porous structure and interconnected transport channels. Zeolitic imidazolate frameworks (ZIF) are a subclass of MOFs. ZIF membranes featuring small aperture sizes have shown promising performance for olefin/paraffin separation. However, the fabrication of thin, defect-free polycrystalline ZIF membranes is still challenging. Therefore, one objective of this research is to prepare high-quality polycrystalline ZIF membranes on low-cost macroporous ceramic supports with high olefin/paraffin selectivities using vapor-phase processing, which combines atomic layer deposition (ALD) and ligand vapor treatment. The second objective is to investigate the properties of the resultant ZIF membranes for separating 1,3-butadiene from C4 hydrocarbon mixtures that include 1,3-butadiene, butenes, and butanes. COFs, a novel class of crystalline porous polymers, have attracted increasing interest due to their unique characteristics, abundant open sites, and interpenetrating channels and cages. Three-dimensional COFs (3D COFs) usually have the characteristics of interpenetration, so their effective pore size can be reduced, thereby achieving more effective separation compared to two-dimensional COFs (2D COFs). It was also reported that COFs are stable in organic solvents owing to the robust covalent linkages (e.g., imine, hydrazine, and ketoenamine) in the frameworks, making them promising porous materials for the preparation of organic solvent nanofiltration (OSN) membranes. Thus, another objective of this research is to prepare 3D COF membranes (e.g., COF-300) that can effectively remove various dyes in organic solvents (e.g., Rose Bengal, Methyl Orange) and to investigate the relationships between interfacial synthesis, membrane structure, and OSN performance. This dissertation entails (1) the synthesis and characterization of ZIF membranes by a vapor-phase seeding method and the study of their olefin/paraffin separation properties, (2) the fabrication of ZIF membranes by all-vapor-phase ligand-induced permselectivation (LIPS) method and secondary growth method for 1,3-butadiene separation from C4 hydrocarbons, (3) the review on the fabrication methods and application fields of 3D COF membranes, and (4) the synthesis and characterization of 3D COF membranes using interfacial polymerization (IP) method and preliminary mechanistic investigation of the solvent transport properties.
Keywords: Covalent organic framework; Gas separation; Membrane separation; Metal-organic framework; Organic solvent nanofiltration